The Analysis of Colloquial Words on Updates Status of Facebook - Mohammad Sofyan Adi Pranata; Feny Nur Fadilah (Surakarta English and Literature Journal, 2021)
The research design of this study is a descriptive qualitative design that on analyzing colloquial words on updates status of facebook from October until December 2020. The objective of the study generally is to find out some types of technical terms used to form colloquial words found on updates status of facebook. They are: Abbreviation, Clipping, Blending, Hypocorism, and Acronyms. Based on the data analysis, from eight types of technical terms presented, five types of technical terms are found by the researcher. The types are not found in the study such as Prefix, Suffix, and combination of Suffix and Prefix. The most frequently used in colloquial words on updates status are Abbreviation, Clipping, and Acronyms. In terms of sociolinguistics, all users of colloquial words in facebook are adult and from educational classes. There are only a few users of colloquial words using colloquial words.